Enhancing Surge Protection Scheme in Distribution Networks of Nepal for Lightning Overvoltage Analysis at Goldhunga Feeder (using EMTP-RV) - Ghimire, Barun; Poudyal, Khem Narayan; Sharma, Shriram; Karki, Navaraj (Journal of Advanced College of Engineering and Management, 2025)
Lightning-induced overvoltages pose a major threat to Nepal’s Integrated Nepal Power System (INPS), particularly in mountainous regions with high lightning activity. This study analyzes surge behavior and mitigation strategies across 132 kV , 66 kV , and 33 kV transmission lines, as well as 11 kV and 0.4 kV distribution networks, focusing on a case study of the 11 kV Goldhunga feeder in Tarkeshwor Municipality, Kathmandu Valley. The feeder is modeled using field data from the Nepal Electricity Authority (NEA), while higher-voltage lines are represented using typical INPS configurations adapted from IEEE/CIGRÉ standards, incorporating NEA-specific conductor types (e.g., ACSR Dog for 33 kV , ACSR Panther for 66/132 kV), tower footing resistance (10–100 Ω), and insulation levels suited to Nepal’s high lightning ground flash density (up to 25.31 strokes/km²). EMTP-RV simulations with 2020–2023 lightning data evaluate critical factors such as Metal Oxide Surge Arrester (MOSA) placement, arrester lead length, TFR, and secondary-side protection. Results show that locating MOSAs within 3 m of transformer terminals, keeping lead lengths below 1 m, and maintaining TFR under 10 Ω significantly reduces peak overvoltages and surge transfer risks, while secondary-side arresters effectively suppress transferred surges to protect transformers and downstream equipment. Conversely, inadequate protection at lower voltages (11 kV and 0.4 kV) causes severe voltage stress and equipment failures. These findings provide a robust, evidence-based framework for optimizing lightning protection in Nepal’s lightning-prone, topographically challenging grid, enhancing reliability, minimizing outages, and offering valuable insights for other mountainous power systems worldwide.